Preparing for Future Pandemics: Challenges for Healthcare Leadership - Abuhammad S (Dove Medical Press, 2022)
Sawsan Abuhammad Maternal and Child Health Department, Faculty of Nursing, Jordan University of Science and Technology, Irbid, 22110, JordanCorrespondence: Sawsan Abuhammad, Email Shabuhammad@just.edu.joBackground: The COVID-19 pandemic is our decade's largest global challenge of health leadership. There is an immediate urge to provide leadership and management with instruction during the extraordinary from before the recovery phase.Aim: To determine the influence of the COVID-19 disease outbreak on leadership challenges during this difficult time.Methods: This review of studies includes the work of scientists who have addressed the challenges of leadership at the time of COVID-19 pandemic. Furthermore, the references to the selected studies were used to locate additional research articles related to the topic challenges for leadership.Conclusion: This new situation of the pandemics needs the leaders in the healthcare system to face many challenges. These challenges are being manager of the care, making decisions, caring for employees, preparing for the unexpected, and updating the community about the situation.Keywords: pandemics, challenges, healthcare, healthcare leadership